2019
DOI: 10.1002/smi.2850
|View full text |Cite
|
Sign up to set email alerts
|

On the role of mindfulness and compassion skills in students' coping, well‐being, and development across the transition to college: A conceptual analysis

Abstract: In this paper, we aim to integrate the current conceptual approaches to stress and coping processes during the college transition with the potential role of mindfulness and compassion (MC) skills on students' well‐being and development. First, we provide an overview of the issues and challenges emerging adults are facing during the transition to college, drawing on the revised version of the transactional stress model by Lazarus and Folkman (1984). Second, we introduce a conceptual model of adaptive stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 116 publications
1
39
0
2
Order By: Relevance
“…Social-emotional competencies within the discourse of teacher education appears broadly within the acknowledgement of higher education as a highly stressful period (Acharya, Jin, and Collins 2018;Bai et al 2020). This has led to the argument that higher education institutions ought to develop students' social-emotional competencies in order to enhance their ability to cope with stress (Bamber et al 2018;Dvořáková, Greenberg, and Roeser 2019). Some studies indeed demonstrated the effectiveness of interventions focused around mindfulness and social-emotional competencies as means for reducing teacher stress and enhancing their inner coping resources (Ergas and Hadar 2019;Birchinall, Spendlove, and Buck 2019;Jennings et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Social-emotional competencies within the discourse of teacher education appears broadly within the acknowledgement of higher education as a highly stressful period (Acharya, Jin, and Collins 2018;Bai et al 2020). This has led to the argument that higher education institutions ought to develop students' social-emotional competencies in order to enhance their ability to cope with stress (Bamber et al 2018;Dvořáková, Greenberg, and Roeser 2019). Some studies indeed demonstrated the effectiveness of interventions focused around mindfulness and social-emotional competencies as means for reducing teacher stress and enhancing their inner coping resources (Ergas and Hadar 2019;Birchinall, Spendlove, and Buck 2019;Jennings et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these first-year students are living on their own and need to take care of themselves for the first time in their lives (Sallis et al, 2008). Moreover, it has been pointed out that when adolescents live away from their parental home, they may experience poor social connections, loneliness, and difficulty in obtaining social support (Wannebo et al, 2018;Dvořáková et al, 2019). This means that living on their own may have a negative impact on their mental health, compared to living at their parental home.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is consistent with the finding that both groups showed the same patterns. Moreover, it is worth noting that students in mindfulness group had less increase in depressive symptoms than those in control group, suggesting that mindfulness practices may potentially have protective effects against stress-related depressive symptoms during academic semester, prepare students to cope with stress and have productive response to stressors (Dvořáková, Greenberg, & Roeser, 2018). This could explain why students in mindfulness group, even though experiencing similar levels of stress as their peers in control group during the finals period, seemed to be more resilient in the face of challenges as indicated by fewer self-reported depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%